2017
DOI: 10.1158/1541-7786.mcr-16-0157
|View full text |Cite
|
Sign up to set email alerts
|

AXL Inhibition Suppresses the DNA Damage Response and Sensitizes Cells to PARP Inhibition in Multiple Cancers

Abstract: Epithelial to mesenchymal transition (EMT) is associated with a wide range of changes in cancer cells, including stemness, chemo- and radio-resistance and metastasis. The mechanistic role of upstream mediators of EMT has not yet been well characterized. Recently, we showed that non-small cell lung cancers (NSCLCs) that have undergone EMT overexpress AXL, a receptor tyrosine kinase. AXL is also overexpressed in a subset of triple-negative breast cancers (TNBCs) and head and neck squamous cell carcinomas (HNSCCs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
66
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 39 publications
11
66
1
Order By: Relevance
“…Recently, a study from our group demonstrated a potential new functional role of AXL in regulating DNA damage response in NSCLC, head and neck cancer, and triple-negative breast cancer models. In that study, the combination of AXL and PARP inhibitors was highly synergistic in cell lines (43). The current study builds upon these findings, highlighting a possible mechanism through which AXL may directly contribute to DDR inhibitor resistance.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, a study from our group demonstrated a potential new functional role of AXL in regulating DNA damage response in NSCLC, head and neck cancer, and triple-negative breast cancer models. In that study, the combination of AXL and PARP inhibitors was highly synergistic in cell lines (43). The current study builds upon these findings, highlighting a possible mechanism through which AXL may directly contribute to DDR inhibitor resistance.…”
Section: Discussionmentioning
confidence: 88%
“…Another recent study unveiled the involvement of an alternative pathway to PI3K, which caused a defect in the HR DNA repairing pathway and sensitized TNBC cell lines to PARP inhibition. The results shed light on the role played by the TAM family receptor tyrosine kinase AXL in epithelial-mesenchymal transition and, for the first time, HR DNA repair pathway, suggesting the use of AXL inhibitors as chemosensitizers in combination with PARP inhibitors in breast cancer [13]. Breast cancer patients with impairment in DNA damage response, HR proteins and BRCA1/2 all harbor a relatively high genomic instability and defective DNA repair machinery; subsequently, they became sensitive to DNA damaging agents such as, PARP inhibitors and platinum agents.…”
mentioning
confidence: 89%
“…A relatively high incidence of germline mutations in the BRCA1/2 genes was reported in TNBCs patients which makes them more sensitive to DNA damaging agents such as platinum and PARP inhibitors, the last of which are particularly active in tumors with defects in DNA HR [1]. Studies provided evidence that targeting key signaling pathways could potentialize the therapeutic effects of the DNA damaging drugs [11][12][13]. The PI3K signaling pathway preserves HR steady state, thus the inhibition of PI3K pathway would result in HR impairment in BRCA-proficient TNBC patients and subsequently sensitize the carcinoma cells to PARP inhibitors.…”
mentioning
confidence: 99%
“…This overexpression of AXL in response to therapy is not unique to these malignant diseases or to PI3K-targeting therapies, as AXL pathway activation has been reported in various cancers that developed resistance to radiotherapy, chemotherapies and EGFR inhibitors (15)(16)(17)(18)(19)(38)(39)(40). Indeed, small molecule inhibitors (such as therapies is superior to that of the monotherapies (15,40,(42)(43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%